Are Students with Mathematics Learning Disabilities Receiving FAPE?: Insights from a Descriptive Review of Individualized Education Programs. Issue 4 (12th September 2020) - Hott, Brittany L.; Morano, Stephanie; Peltier, Corey; Pulos, Joshua; Peltier, Tiffany
Abstract: Students with mathematics learning disability (MLD) are entitled to a free appropriate public education (FAPE) as outlined by their Individualized Education Program (IEP). The IEP is a roadmap to enhance in‐school and postschool outcomes for students with a disability. We reviewed IEPs ( n = 89) for secondary students with MLD enrolled in 15 rural independent school districts in the southeast part of the United States. Results suggested secondary students with MLD have needs in (a) calculation; (b) fractions, decimals, and percentages; (c) functional mathematics; (d) reading; and (e) social and behavioral skills based on annual goals written in their IEPs. Yet 70% of the IEPs reviewed included only instruction in the general education setting, without specialized services. IEPs included a variety of accommodations, but few goals facilitated access to grade‐level content or special education services to support specialized instruction to meet goals. Implications for practice, limitations, and future research are discussed.